2016
DOI: 10.1016/j.mad.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of leucine supplementation in young and aged mice at the onset of skeletal muscle regeneration

Abstract: Aging decreases the ability of skeletal muscle to respond to injury. Leucine has been demonstrated to target protein synthetic pathways in skeletal muscle thereby enhancing this response. However, the effect of aging on leucine-induced alterations in protein synthesis at the onset of skeletal muscle regeneration has not been fully elucidated. The purpose of this study was to determine if aging alters skeletal muscle regeneration and leucine-induced alterations in markers of protein synthesis. The tibialis ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…TA mass and body weights have been previously reported in ageing animals (Perry et al . ,b); in that report, raw TA mass was not different between young and aged animals. However, aged animals presented greater body weights and tibia lengths than did young, such that similar muscle masses were noted despite aged animals being larger.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…TA mass and body weights have been previously reported in ageing animals (Perry et al . ,b); in that report, raw TA mass was not different between young and aged animals. However, aged animals presented greater body weights and tibia lengths than did young, such that similar muscle masses were noted despite aged animals being larger.…”
Section: Resultsmentioning
confidence: 72%
“…, Perry et al . ,b). Therefore, to improve comparison across time we tested the control 18S gene across studies in the same real‐time RT‐PCR run and found no difference in 18S cycle threshold between studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perry et al. () reported that while leucine ingestion combined with exercise may promote protein synthesis, the effects of leucine on protein synthesis are minimal because the signaling pathways involved in hypertrophy are mainly affected by the upregulation of IGF‐1 proteins following exercise. Our results are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%